(3JdbjM GdCdHGH aj CMcGe GdSGHbjf hCgd GdEMJSGHs - (3CHh eMeO YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI GdMSfj Gdjefj,J (B614 (3g` s ((3eMeO Hf CSYO Hf RjO Hf CMeO GdePMLi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi EdgGe MeOg ef ehLHGJ MeOg CeG HYO aEf SDGd GdENhGf GdaVdGA JhLg EdjfG aCLHfG Ydi hLg GdGNJUGQ GdSDGd GdChd s
(3BNQgG (B:s
(3agPG eG EJab ef GdLhGH , hfSCd Gddg hGdeYhfg eY CTZGd YGQVI hTLhf eJfGbVI hGdMeO ddg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B83s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs